Experimental Study on Pre-oxidation of Fine Chemical Wastewater by Optimized Potassium Ferrate Based on Response Surface Method - ZHANG Fakui; WEI Dongyang; LI Jie; XU Weidong; ZHOU Wen (Renmin Zhujiang)
This paper conducts the pre-oxidation treatment for the fine chemical wastewater by potassium ferrate,studies the influence of the dosage of potassium ferrate,pH and reaction time on the COD removal effect by a single-factor parallel experiment,and further optimizes the process conditions with the response surface method.The results show that:The influence degree for the removal rate of COD is as below:reaction time>potassium ferrate dosage>pH.The optimized pre-oxidation conditions are 3.91 g/L of potassium ferrate,4.09 of pH,35.40 min of reaction time,and the COD removal rate is 33.15% under this condition,and the actual verification results of the model are close to the predicted values.Potassium ferrate can effectively degrade refractory organics in wastewater.The B/C value is increased from 0.076 to 0.135,but it has not yet met the requirements of subsequent biochemical treatment.Therefore,other pretreatment technologies or enhanced biochemical processes shall be applied comprehensively.